Rapid and efficient hydrophilicity tuning of p53/mdm2 antagonists - Srivastava, Stuti (2009)
The protein-protein interaction of p53 and mdm2 is an important anticancer target. The interface, however, is very hydrophobic and naturally results in very hydrophobic antagonists. We used the Orru three component reaction (O-3CR) along with a rapid and efficient, recently discovered amidation reaction to dramatically improve the water solubility of our recently discovered low molecular weight p53/mdm2 antagonists. Arrays of amides were synthesized with improved hydrophilicity and retainment and/or improvement of p53/mdm2 inhibitory activity.